Silencing of the Ca(v)3.2 T-type calcium channel gene in sensory neurons demonstrates its major role in nociception - Bourinet, Emmanuel (Nature Publishing Group, 2005)
Analgesic therapies are still limited and sometimes poorly effective, therefore finding new targets for the development of innovative drugs is urgently needed. In order to validate the potential utility of blocking T-type calcium channels to reduce nociception, we explored the effects of intrathecally administered oligodeoxynucleotide antisenses, specific to the recently identified T-type calcium channel family (Ca(V)3.1, Ca(V)3.2, and Ca(V)3.3), on reactions to noxious stimuli in healthy and mononeuropathic rats. Our results demonstrate that the antisense targeting Ca(V)3.2 induced a knockdown of the Ca(V)3.2 mRNA and protein expression as well as a large reduction of ‘Ca(V)3.2-like' T-type currents in nociceptive dorsal root ganglion neurons. Concomitantly, the antisense treatment resulted in major antinociceptive, anti-hyperalgesic, and anti-allodynic effects, suggesting that Ca(V)3.2 plays a major pronociceptive role in acute and chronic pain states. Taken together, the results provide direct evidence linking Ca(V)3.2 T-type channels to pain perception and suggest that Ca(V)3.2 may offer a specific molecular target for the treatment of pain.